Evolution of brown carbon in wildfire plumes. Issue 11 (3rd June 2015) - Forrister, Haviland; Liu, Jiumeng; Scheuer, Eric; Dibb, Jack; Ziemba, Luke; Thornhill, Kenneth L.; Anderson, Bruce; Diskin, Glenn; Perring, Anne E.; Schwarz, Joshua P.; Campuzano‐Jost, Pedro; Day, Douglas A.; et al.
Abstract: Particulate brown carbon (BrC) in the atmosphere absorbs light at subvisible wavelengths and has poorly constrained but potentially large climate forcing impacts. BrC from biomass burning has virtually unknown lifecycle and atmospheric stability. Here, BrC emitted from intense wildfires was measured in plumes transported over 2 days from two main fires, during the 2013 NASA SEAC4RS mission. Concurrent measurements of organic aerosol (OA) and black carbon (BC) mass concentration, BC coating thickness, absorption Ångström exponent, and OA oxidation state reveal that the initial BrC emitted from the fires was largely unstable. Using back trajectories to estimate the transport time indicates that BrC aerosol light absorption decayed in the plumes with a half‐life of 9 to 15 h, measured over day and night. Although most BrC was lost within a day, possibly through chemical loss and/or evaporation, the remaining persistent fraction likely determines the background BrC levels most relevant for climate forcing. Key Points: Biomass burning brown carbon has unknown lifecycle and atmospheric stability Brown carbon and aerosol properties from two fires are measured for 50 h Wildfire brown carbon lifetime was 9–15 h, but a small fraction is stable